SAE Technical Paper Series 2008
DOI: 10.4271/2008-01-0073
|View full text |Cite
|
Sign up to set email alerts
|

An Optical Study of Spray Development and Combustion of Ethanol, Iso-Octane and Gasoline Blends in a DISI Engine

Abstract: In recent times regulatory pressure to reduce CO 2 emissions has driven research towards looking at blending fossil fuels with alternatives such as crop-produced alcohols. The alcohol of interest in this paper is ethanol and it was studied in mixtures with gasoline and iso-octane in an optical sparkignition engine, running at 1500 RPM at low-load operation with 0.5 bar absolute intake plenum pressure. Specifically, tests involved fuels of 100% gasoline and 100% iso-octane, so that differences between multi and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 19 publications
6
25
4
Order By: Relevance
“…In addition, the percentage of ethanol in the total fuelling played a dominant role in affecting the combustion characteristics at light load; however, at full load the DI fuelling percentage became the important parameter, regardless of the percentage of ethanol in the fuel. Some of these findings are different to those of Aleiferis et al [13] with PFI and DI fuelling which showed that DI increased the rate of heat release in general with both gasoline and gasoline/ethanol blends at low-load conditions. One reason for this discrepancy might be that Zhu et al [12] used a low pressure multihole side injector with a nine-hole orifice plate at 20 bar injection pressure compared to the swirl-injector at 80 bar used in [13].…”
Section: Combustion Of Alcohol Blends In Enginescontrasting
confidence: 55%
“…In addition, the percentage of ethanol in the total fuelling played a dominant role in affecting the combustion characteristics at light load; however, at full load the DI fuelling percentage became the important parameter, regardless of the percentage of ethanol in the fuel. Some of these findings are different to those of Aleiferis et al [13] with PFI and DI fuelling which showed that DI increased the rate of heat release in general with both gasoline and gasoline/ethanol blends at low-load conditions. One reason for this discrepancy might be that Zhu et al [12] used a low pressure multihole side injector with a nine-hole orifice plate at 20 bar injection pressure compared to the swirl-injector at 80 bar used in [13].…”
Section: Combustion Of Alcohol Blends In Enginescontrasting
confidence: 55%
“…However, these were set to match nominally as nearly as possible those of previous work published on this engine by the current authors on spray formation and combustion with various fuels, e.g. [18]. The load at 1500 RPM was controlled by throttling to 0.5 bar (±0.01 bar) absolute pressure in the intake plenum.…”
Section: Engine Operating Parametersmentioning
confidence: 99%
“…All timings given in °CA refer to the 'crank angle time equivalent' at 1500 RPM, with one 1 °CA corresponding to 0.111 ms. 1500 RPM corresponded to a mean piston speed of 4.25 m/s. More details about the engine can be found in previous publications [17][18][19].…”
Section: Optical Enginementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, extended discussion will form part of a separate dedicated publication on the basis of [61] where flow field changes with fuelling were studied over a range of conditions and linked by a combination of factors, such as the duration of injection, the droplet velocities and droplet sizes during injection, the fuel spray's shape during injection (e.g. see [19] for spray 'collapse' effects in this engine), etc.…”
Section: Flow Field At Ignition Timingmentioning
confidence: 99%